Influence of moisture in aggregates on properties of cold-mixed resin asphalt mixture. (1st September 2016) - Liu, Xiu; Zhou, Changjun; Feng, Decheng; Tang, Hao; Xu, Yunxi; Fan, Xiaohu
Highlights: The effect of aggregate moisture on cold-mixed resin asphalt mixture was studied. Adhesion between aggregates and resin asphalt is undermined by aggregate moisture. Aggregate moisture affects resin asphalt mixture's stability and flexural behavior. Aggregate moisture can cause bleeding of the resin asphalt mixture under hot weather. Use of quick lime can reduce wet aggregates impact on the resin asphalt mixture. Abstract: Resin asphalt mixture has become increasingly popular as a paving material on long-span bridges in China, due to its sound properties and economic advantages. Typically, the material is mixed and paved under normal temperature with aggregates directly taken from stockpiles exposed to open air. However, such aggregates usually contain moisture which may influence the adhesion between aggregates and asphalt binder. The sessile drop method, column wicking technique, rutting test, indirect tensile test, and three point bending beam test were adopted to experimentally investigate properties of the resin asphalt mixture using wet aggregates. Test results show that moisture in aggregates weakens the adhesion between resin asphalt and aggregates and negatively affects properties of the resin asphalt mixture. In order to minimize the negative effect of aggregate moisture, quick lime was added into resin asphalt mixture. Ensuing tests indicate that quick lime can mitigate the negative influence of aggregate moisture on properties of the resin asphalt mixture. Therefore, addition of quick lime is an effective approach to improve properties of the resin asphalt mixture when mixed with wet aggregates under normal/cold temperature.